The Clinicopathological and Prognostic Value of CCR7 Expression in Breast Cancer Throughout the Literature: A Systematic Review and Meta-Analysis - Mohamed Elhadary; Basel Elsayed; Amgad Mohamed Elshoeibi; Omar Karen; Ibrahim Elmakaty; Jehad Alhmoud; Ahmad Hamdan; Mohammed Imad Malki (Biomedicines)
Background/Objective: This study aimed to determine the clinicopathological findings and prognostic value of chemokine receptor 7 (CCR7) expression in patients with breast cancer (BC). Methods: Up to the 25th of March 2025, a search was conducted using five databases: PubMed, Embase, Scopus, Medline, and Web of Science. The methodological standards for the epidemiological research scale were used to assess the quality of the included articles, and Stata software (Stata 19) was used to synthesize the meta-analysis. Results: We considered 12 of 853 studies that included 3119 patients with BC. High CCR7 expression was not associated with age (odds ratio [OR] 0.82, 95% confidence interval [CI] 0.66–1.03); clinicopathological findings, including tumor size (OR 1.062, 95% CI 0.630–1.791); clinical stage (OR 1.753, 95% CI 0.231–13.304); nodal metastasis (OR 1.252, 95% CI 0.571–2.741); or histological differentiation (OR 1.167, 95% CI 0.939–1.450). CCR7 expression did not affect overall survival (hazard ratio 0.996, 95% CI 0.659–1.505). Conclusions: Our quantitative analysis did not reveal an association between CCR7 expression and poor clinicopathological or prognostic features in BC patients. Because of the high heterogeneity and potential publication bias, large high-quality studies are required to further confirm these findings.